2006
DOI: 10.1073/pnas.0605950103
|View full text |Cite
|
Sign up to set email alerts
|

The Nck-interacting kinase phosphorylates ERM proteins for formation of lamellipodium by growth factors

Abstract: The mammalian Ste20-like Nck-interacting kinase (NIK) and its orthologs Misshapen in Drosophila and Mig-15 in Caenorhabditis elegans have a conserved function in regulating cell morphology, although through poorly understood mechanisms. We report two previously unrecognized actions of NIK: regulation of lamellipodium formation by growth factors and phosphorylation of the ERM proteins ezrin, radixin, and moesin. ERM proteins regulate cell morphology and plasma membrane dynamics by reversibly anchoring actin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(163 citation statements)
references
References 37 publications
7
150
1
5
Order By: Relevance
“…HGC was reported to phosphorylate ERM in the lamellipodium of growth factor-stimulated human epithelial cells (19). Drosophila provides a particularly informative model because of its reduced number of kinases and a single ERM protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HGC was reported to phosphorylate ERM in the lamellipodium of growth factor-stimulated human epithelial cells (19). Drosophila provides a particularly informative model because of its reduced number of kinases and a single ERM protein.…”
Section: Discussionmentioning
confidence: 99%
“…Second, studies in the important model organism Drosophila have implicated a kinase called SLIK, from a very divergent family of kinases, the STE20-related family (STE) (5,6,18). More recently one mammalian kinase in the STE family, HGK, was proposed to function as an ERM kinase (19). Thus, mammalian ERM kinases likely include ones outside the AGC family and in the STE family.…”
mentioning
confidence: 99%
“…The T567D form rescues because it does not require the activation machinery, i.e., it is already in the open conformation to bind to Dbl at the right location, where the membrane is locally tethered to the cytoskeleton. Potential N-ERMAD-interacting partners that contribute to the activation process include the various protein kinases that phosphorylate the conserved C-terminal threonine (myotonic dystrophy kinaserelated Cdc42-binding kinase [Nakamura et al, 2000], protein kinase C␣ [Ng et al, 2001], and Nck-interacting kinase [Baumgartner et al, 2006]) as well as the phosphoinositide PIP 2 (Fievet et al, 2004). PIP 2 (IP 3 head) binding was shown to require several lysine residues from subdomains A and C of N-ERMAD, which form the positively charged molecular surface to interact with the negatively charged membrane inositol polyphosphates and, in the absence of PIP 2 , moesin does not bind CD44 in vitro (Hamada et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This sequence of molecular events releases the intramolecular interaction between the N-and C-termini. Several kinases, including myotonic dystrophy kinase-related Cdc42-binding kinase Several kinases, including myotonic dystrophy kinase-related Cdc42-binding kinase (Nakamura et al, 2000), protein kinase C␣ (Ng et al, 2001), and Nck-interacting kinase (Baumgartner et al, 2006) have been shown to phosphorylate the conserved C-terminal threonine in ERM proteins. This second activation step of phosphorylation may restrict actin tethering by ERM proteins to specialized membrane domains, such as the protruding cell membranes, by locally unmasking the binding site for actin filaments in C-ERMAD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in cellulo, moesin is phosphorylated by Rho kinase during platelet activation [53,54] or by lymphocyte-oriented kinase (LOK) which stimulates lymphocyte migration and polarization [55]. A number of other kinases in vertebrate cells can phosphorylate ERMs on this regulatory threonine, including protein kinase C (PKC) α and θ, Nck-interacting kinase (NIK), human serine/threonine kinase (Mst4) [56][57][58][59]. Phosphorylation of ERM proteins resulted in the localization of these proteins to the actin-rich membrane extensions [53,54,60,61].…”
Section: Biochemical Consideration Of Erm Activation At the Plasma Mementioning
confidence: 99%